2021
DOI: 10.14710/kapal.v18i2.37187
|View full text |Cite
|
Sign up to set email alerts
|

The TLP 2-DOF as an alternative model for extreme wave application

Abstract: Tension Leg Platform (TLP) is an offshore platform structure used for deep-sea oil and gas exploration. The main structure of the TLP consists of a deck, pontoon, mooring system, and foundation. TLP operates in a balance of buoyancy, structural weight, and mooring tension. The problem is the construction of TLP in the deep sea, where sometimes extreme waves appear could damage the TLP structure. This paper proposes a new model of TLP that is more stable to extreme waves. The method is to separate the mass of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The research was conducted on an experimental pool, which is a modified model from our previous research [23], as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…The research was conducted on an experimental pool, which is a modified model from our previous research [23], as shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…Indonesia adalah negara maritim, maka dibutuhkan penguasaan ilmu dan teknologi di bidang ini. Contoh penerapan teknologi maritim adalah struktur anjungan pengeboran minyak lepas pantai, Tension Leg Platform/TLP [1][2][3], sistem perpipaan bawah laut dan kabel jaringan listrik/telekomunikasi bawah laut [4,5]. Bahkan akhir-akhir ini telah berkembang pula kajian tentang penggunaan struktur silinder raksasa untuk terowongan transportasi melintasi selat/danau, yang dikenal dengan istilah Submerged Floating Tunnel Bridge/SFTB [6][7].…”
Section: Pendahuluanunclassified